Assessment of Lifestyle and Health Knowledge of Patients in Duhok Governorate - Iraq - Benyamen, Julian I; S Benyamen, Helen; Dawood, Merna Gh; Elisha, Juliet E; Ali, Ali N (Journal of Pharmacy Practice and Community Medicine)
Background: Lifestyle behaviours and Health literacy are associated with increasing the chronic diseases. This health survey questionnaire was designed to provide a lifestyle assessment and health knowledge of patients in Duhok governorate - Kurdistan Region - Iraq. Methods: A random sample of 200 patients (115 females and 85 males; aged above 50) was selected from public health care centres. The data were collected through a descriptive cross-sectional study by face-to-face questionnaire, between November 2015 - April 2016. The lifestyle practices and health literacy were assessed through several questions about patient demography, health attitudes and knowledge of diseases and treatments. The SPSS V.18 software was used for data analyses. Results: 88.5% of the respondents were diagnosed with chronic illnesses mainly hypertension (53.5%), cardiac attack (29.5%) and diabetes (24%). They have shown their interest on eating fruits and vegetables (88%) rather than consuming high quantities of salty and fatty foods. Nonetheless, the most common adverse habits were lack of physical activities including exercise (85.5%) and healthy walk (56%). Most patients knew little information about their diseases and treatments. Conclusion: An adequate awareness has been shown in taking healthy food, avoiding alcohol consumption and smoking. Nonetheless, there are apparent gaps in patients’ knowledge about the importance of exercise and healthy walk and awareness of their disease conditions and treatments.
Keywords: Patients; Lifestyle; Health; Knowledge; Duhok